2015
DOI: 10.1002/dneu.22357
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and isolation of immature neurons of the adult mouse piriform cortex

Abstract: Physiological studies indicate that the piriform or primary olfactory cortex of adult mammals exhibits a high degree of synaptic plasticity. Interestingly, a subpopulation of cells in the layer II of the adult piriform cortex expresses neurodevelopmental markers, such as the polysialylated form of neural cell adhesion molecule (PSA-NCAM) or doublecortin (DCX). This study analyzes the nature, origin, and potential function of these poorly understood cells in mice. As previously described in rats, most of the PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(71 citation statements)
references
References 55 publications
8
63
0
Order By: Relevance
“…In addition, electron microscopic analysis by Shapiro and colleagueś (2007) revealed that DCX labeled cells had ultrastructural features of immature migrating cells. Third, DCX/PSA-NCAM-expressing cells are negative for mature oligodendroglial, astroglial and microglial markers (Gómez-Climent et al, 2008;Luzzati et al, 2009;Rubio et al, 2015), and very few DCX/PSA-NCAM-expressing cells express NG2 within the piriform cortex (Gómez-Climent et al, 2008;Luzzati et al, 2009;Rubio et al, 2015). Fourth, the expression of DCX/ PSA-NCAM in cortical cells overlaps with other early developmental markers typically found in immature neurons during development, such as TUC-4, TUJ-1, and CNGA3 (Gómez-Climent et al, 2008;Xiong et al, 2008;Luzzati et al, 2009).…”
Section: Most Cortical Dcx/psa-ncam-expressing Cells Are Immature Neumentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, electron microscopic analysis by Shapiro and colleagueś (2007) revealed that DCX labeled cells had ultrastructural features of immature migrating cells. Third, DCX/PSA-NCAM-expressing cells are negative for mature oligodendroglial, astroglial and microglial markers (Gómez-Climent et al, 2008;Luzzati et al, 2009;Rubio et al, 2015), and very few DCX/PSA-NCAM-expressing cells express NG2 within the piriform cortex (Gómez-Climent et al, 2008;Luzzati et al, 2009;Rubio et al, 2015). Fourth, the expression of DCX/ PSA-NCAM in cortical cells overlaps with other early developmental markers typically found in immature neurons during development, such as TUC-4, TUJ-1, and CNGA3 (Gómez-Climent et al, 2008;Xiong et al, 2008;Luzzati et al, 2009).…”
Section: Most Cortical Dcx/psa-ncam-expressing Cells Are Immature Neumentioning
confidence: 90%
“…Whether or not some pyramidal neurons in the adult murine piriform cortex are derived from nonproliferating NG2-expressing cells (Guo et al, 2010;Richardson et al, 2011), does not exclude the contribution of subventricular zone-derived neuroblasts to the generation of neuron-specific nuclear protein (NeuN)-expressing cells in very young rodents (Shapiro et al, 2009;Shapiro et al, 2007a), nor does it exclude that prenatally produced DCX/ PSA-NCAM-expressing cells may also be present in cortical layer II of adult mammals Luzzati et al, 2009;Zhang et al, 2009;Varea et al, 2011;Rossi et al, 2014;Rubio et al, 2015). Given previous disagreements, it is possible that these three cell populations, with an assumed neuronal fate, are present in the healthy adult piriform cortex in different quantities according to age and species (e.g.…”
Section: Limits and Ambiguities Of Cell-proliferation Assays Used To mentioning
confidence: 95%
See 3 more Smart Citations